Fenomena Praktik Joki Skripsi pada Alumni UIN Alauddin Makassar: Tinjauan Hukum Islam - Annisa M; Mustafa, Zulhasari (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2023)
This article aims to find out the reasons why students use thesis jockeys and find out about the actions or practices of remuneration for thesis work services in the perspective of Islamic law at UIN Alauddin Makassar. This type of research is field research or qualitative field research by taking a sociological approach by discussing an object based on students who are the object of research. The sources of data in this study are: 1) Primary data in the form of direct interviews with sources, namely those who use the services of thesis jockeys, 2) Secondary data in the form of data related to this research such as journals, articles, theses, and others. Furthermore, the data collection methods used are interviews, and documentation. Then, the data processing technique is carried out in 3 (three) stages, namely: data checking (editing), data triangulation, and data analysis. Furthermore, data analysis is to collect information and data, distinguish problems and provide an overview and conclude the information that has been collected and then described. The results showed that most of the reasons students used thesis jockeys were due to other activities such as work. And based on a review of Islamic law, it is clear that it is unlawful to use the services of a jockey script because it is not in accordance with the conditions of ijarah.